Hubungan Perhatian Orang Tua dengan Hasil Belajar Siswa Kelas Tinggi UPTD SD Negeri 61 Parepare - Kamaruddin Hasan; Lukman Ali; Ainun Nurul Fadillah (Phinisi Integration Review, 2022)
This research is a quantitative research with the type of correlational research with the following objectives: 1). Knowing the description of parental attention to high grade students at UPTD SD Negeri 61 Parepare, 2). Knowing the description of learning outcomes in high grade students at UPTD SD Negeri 61 Parepare. 3). The relationship between parental attention and learning outcomes for high-grade students at UPTD SD Negeri 61 Parepare. Variable X in this study is parental attention, while variable Y in this study is student learning outcomes. The population in this study were all high school students of UPTD SD Negeri 61 Parepare for the academic year 2021/2022, totaling 50 students. The sampling technique in this study uses a non-probability sampling technique, namely saturated sampling. The research data were obtained by collecting data through a parental concern questionnaire and Student Learning Outcomes Documentation. Data analysis techniques are Descriptive Statistical Analysis and Inferential Statistical Analysis. The results showed that the parents' attention to high grade students at UPTD SD Negeri 61 Parepare was included in the strong category with a percentage of 68% and the learning outcomes of high grade students at UPTD SD Negeri 61 Parepare were included in the very strong category with a percentage of 54%. From the results of inferential analysis obtained the value of sig. 0.257 <0.05 or Ho is rejected and H1 is accepted, which means that there is a significant relationship between parents' attention to the learning outcomes of high grade students at UPTD SD Negeri 61 Parepare. Penelitian ini adalah penelitian kuantitatif dengan jenis penelitian korelasional yang ber-tujuan : 1). Mengetahui gambaran perhatian orang tua pada siswa kelas tinggi di UPTD SD Negeri 61 Parepare, 2). Mengetahui gambaran hasil belajar pada siswa kelas tinggi di UPTD SD Negeri 61 Parepare. 3). Hubungan perhatian orang tua terhadap hasil belajar pada siswa kelas tinggi di UPTD SD Negeri 61 Parepare. Variabel X dalam Penelitian ini adalah Perhatian Orang tua, sedangkan variable Y dalam Penelitian ini adalah Hasil Belajar Siswa. Populasi dalam penelitian ini adalah seluruh siswa kelas tinggi UPTD SD Negeri 61 Parepare tahun ajaran 2021/2022  yang berjumlah 50 siswa. Teknik Pengumpulan Sam-pel pada penelitian ini menggunakan teknin non probability sampling yakni sampling jenuh. Data hasil penelitian diperoleh dengan pengumpulan data  melalui angket per-hatian orang tua dan Dokumentasi Hasil Belajar Siswa. Teknik analisis data adalah Analisis Statistik Deskriptif dan Analisis Statistik Inferensial. Hasil penelitian menunjukkan perhatian orang tua siswa kelas tinggi UPTD SD Negeri 61 Parepare termasuk dalam kat-egori kuat dengaan presentase 68% dan hasil belajar siswa kelas tinggi UPTD SD Negeri 61 Parepaee termasuk dalam kategori sangat kuat dengan presentase 54%. Dari hasil analisis inferensial diperoleh nilai sig. 0,257 < 0.05 atau Ho ditolak dan H1 diterima, yang berarti terdapat hubungan yang signifikan antara perhatian orang tua terhadap hasil belajar siswa kelas tinggi UPTD SD Negeri 61 Parepare.